Breast cancer and communication: monocentric experience of a self-assessment questionnaire - Vittorio Longo; Flavia Abruzzese; Vittoria Miserocchi; Serena Carriero; Anna Clelia Gambaro; Luca Saba; Alessandro Carriero (Journal of Public Health Research, 2022)
Background: The communication of the diagnosis of breast cancer induces to the patient a strong psychological trauma. Radiologists are at the forefront of communicating, either for a biopsy or the probable diagnosis of malignancy. This is a complex task, which requires the knowledge and application of correct "communicative models", among which the SPIKES protocol represents a fundamental reference. Design and methods: 110 patients, with a history of breast cancer, filled out a questionnaire consisting of six questions: five aimed at defining communication compliance with the SPIKES protocol, the sixth, consisting of six feelings, aimed at the knowledge of the next emotional state. Results: Regarding compliance with various "strategic points" of the SPIKES protocol, questionnaires show that 70% of patients reported no omissions, while the remaining 30% reported omissions relatively to perception (56%), emotions (23%), setting (13%), knowledge (6%) and invitation (2%). The results showed the existence of a correlation between the final emotional state and the correct application of the SPIKES protocol; in fact, patients who reacted with a positive final emotional state-reported greater adherence to the strategic points of the SPIKES protocol. Conclusions: In healthcare, knowing the communicative compliance of a team in giving "bad news" is fundamental, especially in breast cancer. The SPIKES protocol is recognized by the Literature as a fundamental reference able to affect "positively" the emotional state of patients. The proposed questionnaire is a valid tool to identify the weak points of communication and related criticalities, to improve clinical practice.